THE INFLUENCE OF EMERGING ADULTHOOD STATUS AND SENSATION SEEKING ON FINANCIAL BEHAVIOR OF PETRA CHRISTIAN UNIVERSITY STUDENTS - Claudia Claudia; Evelyn Setiawan (Finance and Investment Program, School of Business and Management - Petra Christian University, 2020)
This study aims to determine the effect of emerging adulthood status and sensation seeking on students’ financial behavior. This type of research is descriptive with primary data sources. This study was conducted by distributing questionnaires to active undergraduate students at Petra Christian University. The 508 collected data were analyzed using SEM-AMOS 24. The results showed that emerging adulthood status had a significant effect on student’s financial behavior while sensation seeking didn’t have significant effect on students’ financial behavior.